Reference ranges and determinants of testosterone, dihydrotestosterone, and estradiol levels measured using liquid chromatography-tandem mass spectrometry in a population-based cohort of older men - Yeap, B.; Alfonso, Helman; Chubb, S.; Handelsman, D.; Hankey, G.; Norman, P.; Flicker, L. (2012)
Context: Testosterone (T) levels decline with increasing age. Controversy exists over the threshold for classifying T as low vs. normal in older men. The relevance of assessing dihydrotestosterone (DHT) and estradiol (E2) remains unclear. Objective: We assessed the associations of T, DHT, and E2 in men aged 70 yr or older and established reference ranges for these in healthy older men. Participants: Community-dwelling men aged 70-89 yr residing in Perth, Western Australia, Australia, participated in the study. Main Outcome Measures: Plasma T, DHT, and E2 were assayed using liquid chromatography-tandem mass spectrometry in early morning samples from 3690 men. Results: Increasing age, higher body mass index and waist to hip ratio, dyslipidemia, diabetes, and higher LH were independently associated with lower levels of T and DHT. Increasing age, diabetes, and higher LH were associated with lower E2. In a reference group of 394 men aged 76.1 ± 3.2 yr reporting excellent or very good health with no history of smoking, diabetes, cardiovascular disease, cancer, depression, or dementia, the 2.5th percentile for T was 6.4 nmol/liter (184 ng/dl); DHT, 0.49 nmol/liter; and E2, 28 pmol/liter. Applying these cutoffs to all 3690 men, those with low T or DHT had an increased odds ratio for frailty, diabetes, and cardiovascular disease. Men with both low T and DHT had a higher odds ratio for these outcomes. Conclusions: The 2.5th percentile in a reference group of healthy older men provides age-appropriate thresholds for defining low T, DHT, and E2. Additional studies are needed to test their potential applicability and clinical utility in older men. Copyright © 2012 by The Endocrine Society.